L2 CONTROL OF LINEAR SYSTEMS WITH SATURATING ACTUATORS VIA CONVEX OPTIMIZATION APPROACH - Uygur, Ali Fazil; Cansever, Galip (YILDIZ TECHNICAL UNIV, 2011)
Actuator saturation problem in the design of control systems is an important issue to be taken into account. In this study, design of L-2 optimal controller for linear systems under actuator saturation is discussed. Controller is focused to minimizing the L-2 gain of system's performance outputs. Performance specifications that have been taken into design problem and saturation bound on actuators are transformed to constraints which can be expressed in terms of linear matrix inequalities, and the related controller is obtained via solving convex optimization problems over those constraints. Performance of the designed controller is tested via simulation studies for quarter car suspansion model.
Keywords: Actuator saturation; linear matrix inequalities; suspension systems; Engineering